Pengembangan Screencast Presentasi Akuntansi Untuk Siswa SMA - Anam, Khairil; Degeng, I Nyoman Sudana; Sitompul, Nurmida Catherine (Universitas Negeri Malang, 2022)
Interest, attention and motivation of students in doing learning can be made more interesting by using learning media in the form of screencasts. Screencast is the activity of recording from a computer screen display or also called screen capture video with additional narration in the form of audio. In using this media, students can learn independently, because the material can be repeated as needed. Presentation of material that is interesting and clear, does not give people boredom because the learning is coherent according to the learning procedure, is not complicated and can be equipped with practice questions and discussions. Very clear and good voice filling, various images, colors and motion effects add value to the use of this learning media, so that material in lessons that are considered difficult can be completed easily. Students can clearly know the course of the lesson and explain the material. This research development method uses the ADDIE model. This method includes Analysis, Design, Development and Implementation and Evaluation. Validation from media experts, material experts and colleagues, even this media was tested on 34 students/respondents. The conclusion on this media is through the responses of each validator questionnaire so that this media gets results in the form of criteria that are very suitable for use in the learning process.AbstrakMinat, perhatian dan motivasi siswa dalam melakukan pembelajaran dapat dibuat lebih menarik dengan menggunakan media pembelajaran berupa screencast. Sceencast adalah kegiatan merekam dari tampilan layar komputer dari atau disebut juga screen capture video dengan tambahan narasi berupa audio. Dalam menggunakan media ini, siswa dapat melakukan pembelajaran secara mandiri, karena materi bisa diulang-ulang sesuai kebutuhan. Penyajian materi yang menarik dan jelas, tidak memberi rasa bosan bagi karena pembelajarannya runtut sesuai prosedur pembelajaran, tidak berbelit-belit dan bisa dilengkapi latihan soal serta pembahasannya. Pengisian suara yang sangat jelas dan baik, bermacam gambar, warna dan efek gerakan memberi nilai tambah pada pengguaan media pembelajaran ini, sehingga materi pada pelajaran yang dirasa sulit dapat diselesaikan dengan mudah. Siswa bisa mengetahui secara jelas jalannya pelajaran serta penjelasan materi. Metode pengembangan penelitian ini menggunakan model ADDIE. Metode ini meliputi Analisis, Desain, Pengembangan dan Pelaksanaan serta Evaluasi. Validasi dari ahli media, ahli materi dan teman sejawat , media inipun diujicobakan kepada 34 siswa/responden. Kesimpulan pada media ini melalui tanggapan masing-masing angket validator sehingga media ini mendapatkan hasil berupa kriteria yang sangat layak digunakan dalam proses pembelajaran.